Sexism and Religiosity in Croatian Society - Galić, Branka (2007)
The paper presents some results of the research on sexist and religious aspects of gender and religious identity in the Croatian society, carried out on the representative sample in 2004. Four sexist dimensions of gender identity are structures: patriarchalism, androcentrism, declarative agalitarianism and gender egalitarianism.